Socio-Demographic Properties of Employees Working in Rainbow Trout Facilities in Kahramanmaraş - Saler, Serap; Kara, Yüsra (Durmuş Ali ARSLAN, 2023)
This study was carried out to determine the socio-demographic characteristics of the personnel in the rainbow trout farms in Kahramanmaraş province. The study was carried out in 2022 actively working 35 trout farms registered in Kahramanmaraş Provincial Directorate of Agriculture and Forestry. According to the results obtained from the survey study applied to the personnel working in the trout farming facilities, it was determined that the majority of the employees were male and their age range was mostly 40-49, and they constituted 40% of all employees. It was determined that their marital status was mostly married. Single personnel usually live with their families. It has been determined that 47.5% of the personnel working in the enterprises have 3 children. It is seen that 32% of them are primary school graduates and it is understood that their education level is not high. As a result of the surveys applied to the individuals, it was determined that all the personnel in the enterprises have social security. It has been determined that 80% of the working personnel have been working in this profession for less than 10 years, the reason for choosing the profession was yes with 88% when asked whether they wanted to contribute to the family budget and continue their profession with 48%. It has been determined by the survey study that the income level of the personnel working in the enterprises is generally between 5000-7500 TL and the personnel who own the home ownership are in the majority with a rate of 84%.

Bu çalışma, Kahramanmaraş ilinde mevcut bulunan gökkuşağı alabalığı yetiştiriciliği yapılan işletmelerdeki personellere ait sosyo-demografik özelliklerin belirlenmesi amacıyla yapılmıştır. Çalışma 2022 yılında Kahramanmaraş İl Tarım ve Orman Müdürlüğünde kayıtlı olan, faal olarak çalışan 35 adet alabalık yetiştiriciliği yapılan tesislerde gerçekleştirilmiştir. Alabalık yetiştiriciliği yapılan tesislerde çalışan personellere uygulanan anket çalışmasıyla elde edilen sonuçlara göre çalışanların büyük kısmının erkek ve yaş aralıkları çoğunlukla 40-49 olduğu, tüm çalışanların % 40’lık kısmını oluşturdukları belirlenmiştir. Medeni durumlarının ise çoğunlukla evli olduğu tespit edilmiştir. Bekâr olan personeller genellikle aileleri ile birlikte yaşamaktadır. İşletmelerde çalışan personellerin % 47.5’inin 3 çocuğa sahip olduğu saptanmıştır. %32’sinin ilkokul mezunu oldukları görülmekte ve eğitim seviyesinin yüksek olmadığı anlaşılmaktadır. Kişilere uygulanan anket çalışmaları sonucunda, işletmelerdeki personellerin tamamının sosyal güvencesinin var olduğu belirlenmiştir. Çalışan personellerin % 80’inin bu meslekte 10 yıldan az bir süredir çalıştığı, mesleği seçme nedenlerinin ise % 48 ile aile bütçesine katkı olduğu, mesleğe devam etme isteği sorusunu %88 ile evet olarak yanıtladıkları belirlenmiştir. İşletmelerde çalışan personellerin gelir düzeylerinin genellikle 5000-7500 TL arasında olduğu ve ev mülkiyeti kendine ait olan personellerin %84’lük oran ile çoğunlukta olduğu uygulanan anket çalışmasıyla tespit edilmiştir.
Kahramanmaraş İli’ndeki Gökkuşağı Alabalığı Yetiştiriciliği Yapılan İşletmelerde Çalışanların Sosyo-Demografik Özellikleri
Keywords: Agricultural; Veterinary and Food Sciences; Ziraat; Veterinerlik ve Gıda Bilimleri